2020
DOI: 10.1007/s12024-020-00310-8
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy findings in COVID-19-related deaths: a literature review

Abstract: Although many clinical reports have been published, little is known about the pathological post-mortem findings from people who have died of the novel coronavirus disease. The need for postmortem information is urgent to improve patient management of mild and severe illness, and treatment strategies. The present systematic review was carried out according to the Preferred Reporting Items for Systematic Review (PRISMA) standards. A systematic literature search and a critical review of the collected studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
172
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(206 citation statements)
references
References 69 publications
12
172
1
6
Order By: Relevance
“…We found the virus in the olfactory system and in the medulla oblongata ( 26 ). A review of 28 papers by Maiese et al on a total of 341 cases showed alveolar damage with hyaline membrane formation and microthrombi in pulmonary vessels ( 43 ). In a recent autopsy study by Schurink et al in SARS-CoV-2, multiple organs had infected cells, especially in the lungs, but during the disease course these decreased ( 44 ).…”
Section: Clinical Findings: a Glance From The Specialistsmentioning
confidence: 99%
“…We found the virus in the olfactory system and in the medulla oblongata ( 26 ). A review of 28 papers by Maiese et al on a total of 341 cases showed alveolar damage with hyaline membrane formation and microthrombi in pulmonary vessels ( 43 ). In a recent autopsy study by Schurink et al in SARS-CoV-2, multiple organs had infected cells, especially in the lungs, but during the disease course these decreased ( 44 ).…”
Section: Clinical Findings: a Glance From The Specialistsmentioning
confidence: 99%
“…An infected person may exhibit symptoms after an incubation period that can range from about 2 to 14 days (there have been cases up to 29 days). During this time, the infected person is contagious [2,3]. The virus is transmitted through air, in particular through respiratory droplets [4].…”
Section: Introductionmentioning
confidence: 99%
“…In autopsy studies of patients with COVID-19, diffuse alveolar disruption with large vessel thrombi and microthrombi were seen. 4 Dexamethasone (6 mg per day) tends to increase clotting factor and fibrinogen concentrations. Thus, it is plausible for exogenous glucocorticoids to precipitate clinical thrombosis.…”
mentioning
confidence: 99%